2021
DOI: 10.1007/s11528-021-00596-7
|View full text |Cite
|
Sign up to set email alerts
|

K12 Practitioners’ Perceptions of Learning from Failure, Creativity, and Systems Thinking: a Collective Case Study

Abstract: This article presents the results of a collective case study exploring how K12 practitioners perceive the interaction of systems thinking, creativity, and learning from failure within their professional practice. In order to identify K12 practitioners who were well-versed in systems thinking, we targeted students within an instructional design and technology graduate program that included a course on human performance improvement (HPI). At the conclusion of the semester, all students in the course were invited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 31 publications
2
8
0
1
Order By: Relevance
“…According to Randle and Stroink (2018), individuals with high levels of ST may also possess an augmented capability to be more creative. Arrington et al (2021) support this assertion and further maintain that ST is a prowess, which boosts CR. Even though there has been some research on the relationship between ST and CR, more research is needed to confirm this relationship in a new context, such as the hotel industry.…”
Section: System Thinking Creativity and Organizational Sustainabilitymentioning
confidence: 55%
“…According to Randle and Stroink (2018), individuals with high levels of ST may also possess an augmented capability to be more creative. Arrington et al (2021) support this assertion and further maintain that ST is a prowess, which boosts CR. Even though there has been some research on the relationship between ST and CR, more research is needed to confirm this relationship in a new context, such as the hotel industry.…”
Section: System Thinking Creativity and Organizational Sustainabilitymentioning
confidence: 55%
“…This study enriches the existing literature in several ways. As the nature of work failures differs in different industries, scholars have emphasized the trial-and-error process (Bojovic et al , 2018; Lee et al , 2004; Thomke, 1998) or conducted case studies (Amankwah-Amoah et al , 2018; Arrington et al , 2021; Redman and Grieves, 1999) to gain specific knowledge about work failures. However, focusing on specific failure learning limits the generalizability of conclusions drawn for learning from work failures, which may obscure the discovery of common failure-learning characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…CIs are derived from 5,000 bootstrapped resamples. ÃÃÃ p < 0.001 Arrington et al, 2021;Redman and Grieves, 1999) to gain specific knowledge about work failures. However, focusing on specific failure learning limits the generalizability of conclusions drawn for learning from work failures, which may obscure the discovery of common failure-learning characteristics.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…Karakuş (2000) revealed that the creative problem-solving program was effective on the originality dimension of students' creativity. On the other hand, Arrington, Moore, and Bagdy (2021) assert that the educational process can foster the development of creative thinking skills. When the average fluency scores obtained from the worksheets were examined, it was determined that the fluency values in all tasks in the attention and active occupation sections were close to one another.…”
Section: Etik Ile İlgili Hususlarmentioning
confidence: 99%